North Carolina beyond the Connected Age : The Tar Heel State in 2050 - Walden, Michael L. (Michael Leonard), 1951- (Book collections on Project MUSE., 2017)
"North Carolina has been one of the nation's fastest growing states in the last fifty years, and during that time tremendous changes have come to the state's people, industries, jobs, places, environment, and government. Much of this change resulted from the information and technology revolution, which connected the state to the country and the world. We are now moving beyond the connected age--to a new era of living, production, and work--with both new challenges and new opportunities. What will these new transformations mean for North Carolina's people, places, and prosperity? How will the state's population change? What industries will drive the state's economy at mid-century? Will there be enough jobs for workers, and what kinds of jobs? Where and how will we live, and how will we move? How will educational institutions need to adapt and transform to meet the needs of the new economy and workplace? What fuels will power us, and can we find ways to protect the environment?"--